Cellulose nanofiber/deacetylated quaternary chitosan composite packaging film for growth inhibition of Listeria monocytogenes in raw salmon. (March 2023) - Kim, Yeon Ho; Kim, Hyun-Ji; Yoon, Ki Sun; Rhim, Jong-Whan
Abstract: Fully deacetylated quaternized chitosan (DQCTS) was prepared and used as functional fillers in the cellulose nanofiber (CNF)-based films. Field emission scanning electron microscopy (FE-SEM) showed that DQCTS was uniform in the CNF biofilms. The addition of DQCTS with the CNF films changed the surface color and hydrophobicity and significantly enhanced composite films' UV and visible light-blocking properties. Also, the CNF/DQCTS composite films had strong antibacterial activity against Listeria monocytogenes . Raw salmon packaged with the CNF/DQCTS 5% film exhibited potent antimicrobial activity against L. monocytogenes, showing increased lag time for the growth with decreasing specific growth rate (SGR) and maximum population density (MPD) at 4 °C, 10 °C, and 15 °C. Using CNF/DQCTS composite film as active food packaging can potentially extend raw salmon's shelf life. Highlights: Cellulose nanofiber/deacetylated quaternized chitosan (CNF/DQCTS) composite films were prepared. The addition of DQCTS enhanced the CNF film's UV and visible light blocking properties. CNF/DQCTS composite film showed potent antimicrobial activity against L. monocytogenes . Packaging raw salmon with the CNF/DQCTS film extended the shelf life by more than one day.